Analysis of the Impact of The Muaro Jambi Temple Area Development on the Social And Economic Environment of the Local Community - Prillya S, Dona; Mt Napitupulu, Dompak; Fitrah, Yundi (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: The arrangement of cultural heritage areas is an important strategy in preserving historical heritage while encouraging social and economic growth of the community. The Muaro Jambi Temple area, as one of the largest archaeological sites in Southeast Asia, has significant historical, cultural, and spiritual value. Objective: This study aims to analyze the impact of the arrangement of the Muaro Jambi Temple on the physical, social, and economic environment of the community in Muaro Jambi Village and Kemingking Luar Village. Method: The method used is a quantitative descriptive survey approach through the distribution of questionnaires to 43 respondents selected using purposive and simple random sampling techniques. Results and Discussion: The results indicate that the development of the area has had a positive impact on environmental aspects such as infrastructure improvements, waste management, and area conservation. From a social perspective, there has been an increase in community participation, social interaction, and awareness of cultural preservation. Economically, the development of the area has encouraged business opportunities, increased community income, and the growth of both the formal and informal sectors. Conclusion: The development of the Muaro Jambi Temple area has proven significant in improving the social and economic quality of the surrounding community, although further optimization of sustainable planning and comprehensive community involvement is still needed.